2019
DOI: 10.1093/nutrit/nuz059
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in schizophrenia: a systematic review and meta-analysis of 39 studies (N = 5151 participants)

Abstract: Context The pathogenesis of schizophrenia appears to be multifaceted. Objective The aim of this meta-analysis of studies that investigated blood and hair concentrations of trace elements in people diagnosed with schizophrenia was to determine whether levels of trace elements in patients with schizophrenia differ from those in healthy individuals. Data Sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 131 publications
3
27
0
1
Order By: Relevance
“…On the other hand, a 2020 review and meta-analysis of 10 studies with a total of 1784 participants compared blood selenium levels in patients with schizophrenia and healthy controls. The results showed no significant association between schizophrenia and blood selenium levels [ 301 ].…”
Section: Schizophrenia Anxiety and Depressionmentioning
confidence: 99%
“…On the other hand, a 2020 review and meta-analysis of 10 studies with a total of 1784 participants compared blood selenium levels in patients with schizophrenia and healthy controls. The results showed no significant association between schizophrenia and blood selenium levels [ 301 ].…”
Section: Schizophrenia Anxiety and Depressionmentioning
confidence: 99%
“…5,6 Some investigators have recently reported that SCZ is accompanied by changes in trace/metal elements, although contradictory results were obtained with different types of metals, SCZ, and methods. [11][12][13][14][15] Importantly, Cai et al 15 found a significant reduction in serum levels of the alkali metal cesium in individuals with SCZ in comparison with healthy controls. This may be important because cesium shares some similarities with potassium, and therefore may interfere with potassium metabolism, 16 while a single nucleotide polymorphism (SNP) in the KCNH2 gene, which encodes the pore-forming subunit of potassium channels, has been associated with SCZ and with cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic amount of Mn called manganism can also manifest itself by early psychotic symptoms [11]. Rats developed schizophrenialike behaviors after large administration of manganese chloride [12]. This is caused by the ability of Mn to produce free radicals and then, consequently, contribute to neurodegeneration [13].…”
Section: Introductionmentioning
confidence: 99%
“…NO can cause free radical-mediated neurotoxicity and can be found in high concentrations in patients with schizophrenia [20,21]. Consequently, researchers try to estimate to what extent manganese playsa role in the arginine-NO pathway and if it can be used in treatment [12].…”
Section: Introductionmentioning
confidence: 99%